0543 Comparison Of Fixed Pressure Vs. Auto-titrating Cpap For Patients With Suboptimal Cpap Titrations. (27th April 2018) - Diamond, M; Khanna, S; Jaffe, F; Chatilla, W; Weaver, S; Vega-Sanchez, M; Sharif, T; D'Alonzo, G E; Diaz-Abad, M; Krachman, S
Abstract: Introduction: The American Academy of Sleep Medicine defines an optimal continuous positive airway pressure (CPAP) titration as a pressure that results in a respiratory disturbance index (RDI) < 5 events/hr maintained for at least 15 minutes with supine REM sleep. Many patients achieve an RDI < 5 events/hr for 15 minutes but do not have REM supine sleep at the recommended pressure. In these cases, patients are prescribed the perceived best CPAP pressure or placed on auto-titrating CPAP. It is unclear which treatment is superior. Methods: We conducted a retrospective analysis of patients who presented for a CPAP titration or split night study between 6/1/17–8/1/17. The lowest pressure (optCPAP) that reduced the RDI to < 5 events/hr was determined. Studies were optimal if 15 minutes of supine and REM sleep was recorded at optCPAP and suboptimal if these criteria were not met. Treatment modalities for all studies (auto or fixed pressure) were determined and compliance and residual RDI obtained from smart card data. Treatment failure was defined as a residual RDI >5 at 1 month with less than 5% of nights spent with a large leak. Results: A total of 209 patients presented for a CPAP titration or split night study. In 172(82%), an optCPAP was determined. There were 102 (61%) optimal studies and 67(39%) suboptimal studies. There was no statistically significant difference in Age, BMI, severity of OSA or Epworth score. Patients with suboptimal studies were predominately female (75% vs 57%, p=0.02) with lower sleep efficiencies (78% vs 83%, p<0.001). One hundred and one patients (59%) had compliance data at 1 month, of which 41 were suboptimal. Seventeen suboptimal patients received Auto-titrating CPAP and 24 patients a fixed pressure. There was no significant difference in treatment failures between fixed and auto-titrating CPAP (16% Vs 17%) even when compared to failures in the optimal group (15%). Conclusion: Both fixed pressure and auto-titrating CPAP are equally effective at normalizing RDI at 1 month and are acceptable for suboptimal titration studies. Support (If Any): None.